2004
DOI: 10.1111/j.1365-2958.2004.04189.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel extracellular phospholipase C of Pseudomonas aeruginosa is required for phospholipid chemotaxis

Abstract: SummaryPseudomonas aeruginosa and other bacterial pathogens express one or more homologous extracellular phospholipases C (PLC) that are secreted through the inner membrane via the twin arginine translocase (TAT) pathway. Analysis of TAT mutants of P. aeruginosa uncovered a previously unidentified extracellular PLC that is secreted via the Sec pathway (PlcB). Whereas all presently known PLCs of P. aeruginosa (PlcH, PlcN and PlcB) hydrolyse phosphatidylcholine (PC), only PlcB is active on phosphatidylethanolami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 45 publications
2
74
0
Order By: Relevance
“…This alginate prevalence indicates that isolated strains of animal products are involved in the formation of biofilms as alginates have been widely regarded as the major exopolysaccharides of the biofilm matrix [24,25]. The prevalences of plcH (71.0%) gene showed that strains isolated were able of secreting hemolytic exoenzyme and phospholipase C and thus strains could be involved in pulmonary infections [26,27]. Our results obtained in this study correlate with those proved by Bradbury et al [28] who proved that P. aeruginosa isolated from nosocomial infections were found to have an increased prevalence of virulence genes.…”
Section: Discussionmentioning
confidence: 99%
“…This alginate prevalence indicates that isolated strains of animal products are involved in the formation of biofilms as alginates have been widely regarded as the major exopolysaccharides of the biofilm matrix [24,25]. The prevalences of plcH (71.0%) gene showed that strains isolated were able of secreting hemolytic exoenzyme and phospholipase C and thus strains could be involved in pulmonary infections [26,27]. Our results obtained in this study correlate with those proved by Bradbury et al [28] who proved that P. aeruginosa isolated from nosocomial infections were found to have an increased prevalence of virulence genes.…”
Section: Discussionmentioning
confidence: 99%
“…Protease IV also degrades surfactant proteins A, B, and D, which are important for surface tension and innate immunity (35). The phospholipases PlcB, PlcH, and PlcN target the mucus layer and cell membrane, facilitating bacterial transit through the mucus layer and liberating nutrients exploited by the bacteria (36)(37)(38). Furthermore, PlcH has been shown to suppress the neutrophil respiratory burst, which may also facilitate P. aeruginosa survival (39).…”
Section: Infection Maintenancementioning
confidence: 99%
“…Twitching motility chemotaxis assays were performed as previously described (3,13). In brief, twitching assay plates containing buffered agar (10 mM Tris, pH 7.6; 8 mM MgSO 4 ; 1 mM NaPO 4 , pH 7.6; and 1.5% agar) were allowed to dry overnight at 25°C before 4-l spots of 10 mg/ml PE, 20 mg/ml LCFA, or 0.72 mg/ml BALF were placed on the agar …”
Section: Methodsmentioning
confidence: 99%